2018
DOI: 10.1038/s41380-018-0294-z
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a bifactor model of oppositional defiant disorder

Abstract: Dimensions of irritability and defiant behavior, though correlated within the structure of ODD, convey separable developmental risks through adolescence and adulthood. Irritability predicts depression and anxiety, whereas defiant behavior is a precursor to antisocial outcomes. Previously we demonstrated that a bifactor model comprising irritability and defiant behavior dimensions, in addition to a general factor, provided the best fitting structure of ODD symptoms in five large datasets.1 Herein we extend our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…Hypothesis 1 : We hypothesize that the general factor within a bifactor model will not be influenced equally by all psychopathology dimensions and instead will be defined primarily by distress (Oltmanns et al, 2018) and antagonism-imbued forms of externalizing (i.e., conduct disorder, oppositional defiant disorder). We predicted that antagonism-imbued forms of externalizing would load highly onto the general factor given that our demonstration relies on youth data and antagonism and neuroticism tend to be more highly correlated and thus more difficult to disentangle in youth compared with adults (Tackett, Kushner, De Fruit, & Mervielde, 2013; Waldman et al, 2018).…”
Section: Riskier Tests Of the Validity Of The Bifactor Model Of Psychopathologymentioning
confidence: 99%
“…Hypothesis 1 : We hypothesize that the general factor within a bifactor model will not be influenced equally by all psychopathology dimensions and instead will be defined primarily by distress (Oltmanns et al, 2018) and antagonism-imbued forms of externalizing (i.e., conduct disorder, oppositional defiant disorder). We predicted that antagonism-imbued forms of externalizing would load highly onto the general factor given that our demonstration relies on youth data and antagonism and neuroticism tend to be more highly correlated and thus more difficult to disentangle in youth compared with adults (Tackett, Kushner, De Fruit, & Mervielde, 2013; Waldman et al, 2018).…”
Section: Riskier Tests Of the Validity Of The Bifactor Model Of Psychopathologymentioning
confidence: 99%
“…Specifically, in youth samples, twin studies have shown high heritabilities (h 2 ) and moderate levels of nonshared environ mental influences, but nonsignificant shared environmental influences, for ADHD (h 2 =~6080%) 94 and ODD (h 2 =~3070%) 93 , as well as for psychopathic traits (such as callousunemotion ality and narcissism) 95 . These studies have also found moder ate heritability (h 2 =~50%), shared environmental influences, and nonshared environmental influences for CD 96 , and moderate heritability for various forms of youth antisocial behavior, includ ing rule breaking and aggression 97 , with its various forms such as reactive, proactive and relational aggression 96,98,99 .…”
Section: Behavior Genetic Evidencementioning
confidence: 99%
“…Although irritability is not a defining diagnostic feature, impairments in irritability are highly prevalent in childhood ADHD and affect at least half of patients in clinical samples [28][29][30]. Irritability is also strongly associated to defiant behaviours [31], and as such defined as a dimension of ODD in the DSM-5 [16].…”
Section: Introductionmentioning
confidence: 99%